The Effect of Service Quality And Facilities on Customer Satisfaction - Ferdinandsyah, Azka; Fadili, Dadan Ahmad (International Journal of Education, Information Technology, and Others, 2024)
Abstract Consumer satisfaction at Villa Cemara Situ Gunung can be influenced by many factors, including the quality of service and facilities. The existence of good service quality and complete facilities can certainly increase consumer satisfaction. This research aims to determine the influence of Service Quality and Facilities on Consumer Satisfaction at Villa Cemara Situ Gunung. The research method used is a descriptive verification method with a quantitative approach. The test stages used are validity test, reliability test, classical assumption test, multiple linear regression analysis technique and hypothesis testing using the t test, f test and coefficient of determination using SPSS 25 tools with the main data source being questionnaires distributed to consumers who are staying overnight. at Villa Cemara in 2023 there will be 230 respondents. The results of the descriptive analysis show that Service Quality has a total average score of 822.2 which is included in the "good" category. For the Facility variable, there was a total average value of 833.6 which is included in the "good" category. As for the Consumer Satisfaction variable, it shows a total average value of 876.5 which is included in the "good" category. The results of the verification analysis show that there is a partial influence between Service Quality on customer satisfaction by 17.4%, there is a partial influence between Facilities on Customer Satisfaction by 22.4%. The simultaneous effect of Service and Facility Quality on Customer Satisfaction is 59.4% and the remaining 40.6% is influenced by other variables. Keyword: Service Quality, Facilities, and Consumer Satisfaction Abstrak Kepuasan Konsumen pada Villa Cemara Situ Gunung dapat dipengaruhi oleh banyak faktor, diantaranya yaitu Kualitas Pelayanan dan Fasilitas. Adanya Kualitas Pelayanan yang baik dan Fasilitas yang lengkap tentunya dapat meningkatkan Kepuasan Konsumen. Penelitian ini bertujuan untuk mengetahui pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Konsumen pada Villa Cemara Situ Gunung. Metode penelitian yang digunakan yaitu metode deskriptif verifikatif dengan pendekatan kuantitatif. Tahap uji yang digunakan adalah uji validitas, uji reliabilitas, uji asumsi klasik, Teknik analisis regresi linear berganda dan uji hipotesis menggunakan uji t, uji f dan koefisien determinasi dengan menggunakan alat bantu SPSS 25 dengan sumber data utama kuesioner yang disebarkan kepada konsumen yang sedang menginap di Villa Cemara pada tahun 2023 sebanyak 230 responden. Hasil analisis deskriptif menunjukkan bahwa Kualitas Pelayanan memiliki total nilai rata-rata sebesar 822,2 yang mana nilai ini termasuk dalam kategori “baik”. Untuk variabel Fasilitas didapati total nilai rata-rata sebesar 833,6 yang mana nilai ini termasuk kategori “baik”. Sedangkan untuk variabel Kepuasan Konsumen menunjukan total nilai rata-rata sebesar 876,5 yang mana nilai ini termasuk kategori “baik”.Hasil analisis verifikatif menunjukkan bahwa terdapat pengaruh parsial antara Kualitas Pelayanan terhadap kepuasan konsumen sebesar 17,4%, terdapat pengaruh parsial antara Fasilitas terhadap Kepuasan Konsumen sebesar 22,4%. Pengaruh simultan Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Konsumen sebesar 59,4% dan sisa 40,6% lainnya dipengaruhi oleh variabel lain. Kata Kunci: Kualitas Pelayanan, Fasilitas, Dan Kepuasan Konsumen